Kejenuhan Belajar Mahasiswa Jurusan Bimbingan dan Konseling Islam Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci - Saaduddin Saaduddin (Journal on Education, 2022)
This study aims to look at the description of the learning saturation of male students, the learning saturation of female students, and to test the differences in learning saturation of male and female students in the 2014, 2015, 2016 and 2017 Islamic Guidance and Counseling Department of the Faculty of Tarbiyah and Teacher Training IAIN Kerinci. This type of research is descriptive and comparative research which describes the differences in learning saturation of male and female students. The study population consisted of 480 students of the Department of Islamic Guidance and Counseling, Faculty of Tarbiyah and Teacher Training Sciences at IAIN Kerinci who were still enrolled in the 2016/2017 academic year, with a total sample of 218 people, sampling using the Proportional Stratified Random Sampling technique. The instrument used was a questionnaire with a Likert scale model and processed through statistical techniques with a percentage formula. To see the difference in learning saturation of male and female students, the t test technique was used. The findings of the study show that: (1) student learning saturation of the Islamic Guidance and Counseling Department of the Faculty of Tarbiyah and Teacher Training IAIN Kerinci is generally in the medium category, (2) male students' learning saturation is in the medium category, (3) student learning saturation women are in the medium category, and (4) there are differences in learning saturation of male and female students with a significant 0.084, the t count is 2,306 with degrees of freedom (df) 216 the value of the t table of 5% significance is 1,653. Based on the results of this study, the researchers suggested to counseling/counselor lecturers to be able to apply various types of services to students who are experiencing boredom so that these students can actually see the situation and conditions they are facing, rationalize the way students think so they can control themselves well.